THE INFLUENCE OF INFRASTRUCTURE ON INEQUALITY OF INCOME DISTRIBUTION IN EASTERN INDONESIA - Laraibaphy, Albani Elha; Ahmad, Abdul Aziz; Suharno, Suharno (Al-Mustashfa: Jurnal Penelitian Hukum Ekonomi Syariah, 2023)
AbstractThis quantitative research was on income inequality and infrastructure in Eastern Indonesia. This study investigates the impact of road, electricity, water, telecommunication, housing, education, and health infrastructure on income inequality from 2012 to 2018. Using panel data from 16 Eastern Indonesia provinces with 96 observations, this study combines cross-sectional data from 16 Eastern Indonesia provinces and six years of time-series data (2012, 2013, 2014, 2015, 2017, 2018). The results from the Fixed Effect Model by Panel Data indicate that (1) Road, electricity, water, housing, education, and health infrastructure were not significantly correlated with income inequality, and (2) Telecommunication infrastructure harmed income inequality. The implication is that in achieving a more just income distribution, the government should reexamine the distribution of infrastructure projects, i.e., road, electricity, water, housing, education, and health, that are being built. This can be done by focusing the projects on less developed areas.Keywords: Income Inequality; Infrastructure; Eastern Indonesia.